CONFRONTED PATRIARCHY IN SYLVIA PLATHS POEMS - Kukuh Prayitno Subagyo (TEFLIN Journal: A publication on the teaching and learning of English, 2009)
Abstract: The American literary canons, mainly those of the nineteen fifties and the nineteen sixties, had consistently portrayed women as subservient citizens. Women in the American culture had been put under menÃ¢â¬â¢s domination and thus lost their identity and been unable to determine their own fate. They played roles long prescribed by men, both in the home and in their social milieu. As products of the era, a number of Sylvia PlathÃ¢â¬â¢s poems depict confrontation against this phenomenon of patriarchy in which women have been inferior to and abused by men; they fight for freedom and to regain their true roles as women and human beings.